Evidential Modification of a Statement in a News Discourse: A Functional Aspect - A. I. Chepurnaya (Tsentr nauchnykh i obrazovatelnykh proektov, 2020)
The results of a study of the modalization of statements in terms of reportative evidentiality in the news discourse based on the material of Russian, English and German-language articles are presented in the article. Particular attention is paid to the functions of quoted or reported speech and indicators of reportative evidentiality, which are considered as two components that make up the structural-semantic whole of statements with quotation inclusions. The novelty of the study is in an attempt to conduct a comprehensive study of the functional aspect of reportative-evidential modification of the utterance. The relevance of the study is due to the importance of the information and news genres of media discourse in modern society, as well as the insufficient development of the functional aspect of reportative-evidential modalization of the utterance in the news discourse for all the high frequency of quotation inclusions in the texts of this genre. A classification is proposed that includes eight functions: three functions of the evidential framework (meta-informing, increasing the recipient's trust in the reliability of the message and delegation of responsibility) and five functions of quoted and reported speech (informative, synthesizing, expressive-evaluative, nominative, argumentative). The conclusion about the interconnectedness of the selected functions among themselves, as well as about the possibility of implementing several functions within the framework of one utterance and in each case introducing into the utterance both reported speech and reportative evidentials is drawn.